Reforma PIT - implikacje dla finansów publicznych - Arendt, Łukasz (Personal Income Tax Reform - Implications for Public Finance, 2005)
The objective of the paper is to present selected issues concerning personal income tax reform in Poland. The problem is complicated because of the current state of public finance, when the ability to fullfill the Maastricht criteria - the conditions of accession to the EMU, seems to vanish. In this situation the tax reform should be neutral for public sector income, which is not always connected with other postulates towards personal income tax and its role for the economic growth.The paper presents a simulation of various variants of flat-progressive tax and their effect for the incomes of public finance sector. The results of the analysis let to draw a conclusion that the effects of the introduction of the flat-progressive tax depend first of all on the taxpayers reaction to the changes. The main role will be played by the taxpayers from the first tax bracket, who make up about 95% of the all taxpayers.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1071, t. 2, s. 379-395